Regioselective Synthesis of Phenoxathiin Derivatives under Transition-Metal-Free Conditions - Hu, Fangdong; Zhao, Xin; Li, Yanqiu; Feng, Lei; Ma, Chen (Synthesis, 2013)
A simple and efficient method was developed for the synthesis of phenoxathiin derivatives. A range of 1,2-dihaloarenes or 1-halo-2-nitroarenes reacted with 2-sulfanylphenol to give the desired products in good-to-excellent yields. It is intriguing that 1-halo-2-nitroarenes containing electron-donating groups worked well as substrates in this reaction.
Keywords: regioselectivity; heterocycles; polycycles; cyclizations; fused-ring systems